2014
DOI: 10.1136/jech-2014-204083
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of inequality in disability-free expectancy at birth and age 85 across space and time in Great Britain

Abstract: BackgroundAlthough mortality and health inequalities at birth have increased both geographically and in socioeconomic terms, little is known about inequalities at age 85, the fastest growing sector of the population in Great Britain (GB).AimTo determine whether trends and drivers of inequalities in life expectancy (LE) and disability-free life expectancy (DFLE) at age 85 between 1991 and 2001 are the same as those at birth.MethodsDFLE at birth and age 85 for 1991 and 2001 by gender were calculated for each loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 17 publications
0
16
0
3
Order By: Relevance
“…Although direct comparisons of DFLE across different countries are somewhat problematic due to methodological differences (e.g., MSLTs vs Sullivan’s method) and differences in outcome measures of disability and/or morbidity [56], it is useful to place our findings in the context of other research on DFLE in the oldest-old. Findings from Great Britain [57], Denmark [58], and the USA [59] suggest that oldest-old individuals in these countries are living longer and with fewer years of disability, than in previous years, though there is some evidence of countervailing trends in younger ages [60]. However, trends in the oldest-old have been mixed in other countries; for example, in Sweden, one study found that oldest-old individuals are living longer and with less disability [61], while another found stagnation in ADL disability and declines in physical functioning [62].…”
Section: Discussionmentioning
confidence: 99%
“…Although direct comparisons of DFLE across different countries are somewhat problematic due to methodological differences (e.g., MSLTs vs Sullivan’s method) and differences in outcome measures of disability and/or morbidity [56], it is useful to place our findings in the context of other research on DFLE in the oldest-old. Findings from Great Britain [57], Denmark [58], and the USA [59] suggest that oldest-old individuals in these countries are living longer and with fewer years of disability, than in previous years, though there is some evidence of countervailing trends in younger ages [60]. However, trends in the oldest-old have been mixed in other countries; for example, in Sweden, one study found that oldest-old individuals are living longer and with less disability [61], while another found stagnation in ADL disability and declines in physical functioning [62].…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, the only studies on this issue that incorporated a time dimension did not break down the population by migrant origin (Wohland et al 2014; Fouweather et al 2015; Hu et al 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Kim (Kim 2014) constructed a similar indicator (probability of reaching 100 years) and found it was highly correlated with socioeconomic factors, such standard of living, as well as health care expenditure and. Looking at other endpoint (healthy life expectancy-HLE-at old ages), three studies found that material deprivation, as well as health care expenditure, explained cross-national HLE inequalities across Europe (Fouweather et al 2015;Wohland et al 2014). The influence of socioeconomic deprivation later in life has also been confirmed by individual level studies, recently summarized in a literature review (Huisman et al 2013).…”
Section: Discussionmentioning
confidence: 87%
“…Therefore, survival rates at older ages constitute a good indicator of overall population health and development (Huisman et al 2004). Although studies among younger groups are relatively common few investigations have, to date, examined the role of socioeconomic factors on the inequalities in life expectancy and mortality among older age groups (Fouweather et al 2015;Huisman et al 2004;Kim 2014;Wohland et al 2014). Nonetheless, there are important reasons to evaluate socioeconomic inequalities in health at advanced ages.…”
Section: Introductionmentioning
confidence: 99%